2019
DOI: 10.1111/sms.13514
|View full text |Cite
|
Sign up to set email alerts
|

Physical training, UCP1 expression, mitochondrial density, and coupling in adipose tissue from women with obesity

Abstract: Background: Exercise training may improve energy expenditure, thermogenesis, and oxidative capacities. Therefore, we hypothesized that physical training enhances white adipose tissue mitochondrial oxidative capacity from obese women. Objective: To evaluate mitochondrial respiratory capacity, mitochondrial content, and UCP1 gene expression in white adipose tissue from women with obesity before and after the physical training program. Methods: Women (n = 14, BMI 33 ± 3 kg/m 2 , 35 ± 6 years, mean ± SD) were subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 44 publications
0
18
0
4
Order By: Relevance
“…Mitochondrial respiration capacity in human exercise intervention studies is not exclusive to skeletal muscle samples. Although such investigations are less common, different studies have measured respiration capacity in adipose tissue, 21,22 and blood cells (including lymphocytes and platelet). [23][24][25][26] Tests run in duplicates (or more) enable researchers to capture technical variability, and/or biological day-to-day variability within participants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial respiration capacity in human exercise intervention studies is not exclusive to skeletal muscle samples. Although such investigations are less common, different studies have measured respiration capacity in adipose tissue, 21,22 and blood cells (including lymphocytes and platelet). [23][24][25][26] Tests run in duplicates (or more) enable researchers to capture technical variability, and/or biological day-to-day variability within participants.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial respiration capacity in human exercise intervention studies is not exclusive to skeletal muscle samples. Although such investigations are less common, different studies have measured respiration capacity in adipose tissue, and blood cells (including lymphocytes and platelet) …”
Section: Introductionmentioning
confidence: 99%
“…The search process identified eight eligible studies conducted in humans and 19 eligible studies conducted in animals (see supplement) [19]. Four of the studies in humans [16][17][18]39] together with data from study 5 provided data for a meta-analysis showing no effect of chronic exercise on UCP1 mRNA (p > 0.05; no data were available to test this hypothesis for UCP1 protein expression). Seven of the studies in animals identified in the systematic review that used a normal diet [11][12][13][14][15]40,41] provided data for a meta-analysis showing no effect of chronic exercise on UCP1 mRNA (p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Treadmill training for a longer duration (8-9 weeks), however, yields much more inconclusive results, with increases [21], no changes [94,184], and decreases all observed [22,95]. Both swimming and running protocols up to 8 weeks consistently increased [8, 21, 22, 56, 81, 95, 98-101, 111-113, 185] or yielded insignificant changes [8,22,99,111,180,185] in UCP1, although longer durations (10 weeks) did not change UCP1 concentrations [114,115,137].…”
Section: Dissimilarities Between Cold Exposure and Exercisementioning
confidence: 99%
“…Though FGF21 is mainly released by hepatocytes into circulation [119], its expression can be induced in skeletal muscle in response to acute exercise [120,121]. A co-receptor of FGF21, ßKlotho, is a singletransmembrane protein essential for FGF21 activity, which is abun- R [180] ↑mRNA in sWAT swim training (30d) R [100] ↑mRNA, protein in iWAT treadmill training (5 wk) R [56], [98] ↑mRNA in sWAT resistance training (8 wk) R [199] ↑mRNA in sWAT aerobic training (8 wk) R [200] ↑mRNA in sWAT treadmill (8 wk) R [22], [95], [185] mRNA in vWAT treadmill (8 wk) R [22], [185] ↑mRNA in eWAT treadmill training (8 wk) R [21] ↑protein in eWAT treadmill training (8 wk) R [112] ↑mRNA in iWAT treadmill training (8 wk) R [113] ↑protein in iWAT voluntary wheel running (10 wk) R [114] protein in eWAT voluntary wheel running (10 wk) R [114] mRNA in eWAT resistance, endurance training (10 wk) R [115] mRNA in sWAT endurance, interval training (10 wk) dantly found in adipose tissue, but not skeletal muscle [122,123]. This enables FGF21 to have unique actions on adipose tissue and skeletal muscle upon release [124].…”
Section: Fibroblast Growth Factor-21mentioning
confidence: 99%